Temporal Ordering and Auditory Resolution in Individuals with Sensorineural Hearing Loss - Andrade, Adriana Neves de; Sanfins, Milaine Dominici; Skarzynska, Magdalena Beata; Skarzynski, Piotr Henryk; Gil, Daniela (International Archives of Otorhinolaryngology, 2023)
Introduction Peripheral hearing loss, besides causing inadequate auditory input, can lead to distortions in the tonotopic auditory map and reorganization of neural networks. Therefore, the processing of temporal aspects of a sound stimulus and, consequently, the effectiveness of human communication can be negatively impacted.Objective To test the temporal ordering and auditory resolution of people with mild and moderate sensorineural hearing loss and to compare them with the those of people with normal hearing.Methods A total of 19 right-handed individuals aged 16 to 59 years with mild to moderate postlingually acquired symmetric bilateral sensorineural hearing loss participated in the study. They were submitted to frequency and duration pattern tests and a random gap detection test.Results The mean correct response rate in the frequency pattern test was of 66.3%, and, in the duration pattern test, 71.7%. The mean threshold in the random gap detection test was of 14.1 ms. A comparison with the criteria established for normal subjects without peripheral hearing loss revealed that more than half the subjects had abnormal results in the temporal ordering test, while a smaller fraction had reduced temporal resolution.Conclusions The performance of the subjects with acquired sensorineural hearing loss was poorer than that of the participants without peripheral hearing loss. Their results on the temporal ordering test were also poorer than in the temporal resolution test, demonstrating the importance of analyzing both these auditory skills in people with peripheral hearing loss.
Keywords: hearing; hearing tests; auditory perception; sensorineural hearing loss; time perception; auditory perceptual disorders